Actively Tunable Structural Color Rendering with Tensile Substrate. Issue 9 (29th March 2017) - Song, Shichao; Ma, Xiaoliang; Pu, Mingbo; Li, Xiong; Liu, Kaipeng; Gao, Ping; Zhao, Zeyu; Wang, Yanqin; Wang, Changtao; Luo, Xiangang
Abstract : Dynamic color tuning is a very important and fascinating direction in the field of structural colorations due to its possible applications in stealth, anticounterfeiting, displaying techniques, etc. However, the most recent work about structural colors either have limitations on dynamic frequency tunability or require special conditions. In this work, a tensile substrate (e.g., polydimethylsiloxane) is introduced into conventional plasmonic structures to demonstrate dynamic tunable structural colors. The proposed idea is experimentally realized by fabricating samples via interference photolithography. The results show that resonance‐induced colors can be dynamically tuned from green to fuchsia by stretching the tensile substrate. Moreover, a further thematic analysis of the physical mechanism in the proposed structure is conducted. The authors envisage that their method has potential applications in anticounterfeiting, biometric sensors, and mechanics measurements. Abstract : A tensile substrate is introduced into the conventional plasmonic structure to propose an effective method for tunable structural colors. By controlling the external force, color varying from green to fuchsia is achieved. The presented findings may have great potential applications in displays, biometric sensors, and mechanics measurement, etc.